Plan de negocios mediante el estudio de mercado para proponer la creación de las Cabañas Comunitarias Shanshu Hoatzín, en el sector Orillas de la Laguna Limoncocha, Sector Este, Cantón Shushufindi - García Marín, Edwin Rigoberto (2018)
The research had as a main objective to design a business plan, to propose the creation of the "Shanshun hoatzin" community cabins, in Limoncocha parish, which is full of natural and cultural riches. It is a community icon of the tourism in the Canton, for that reason it was carried the present research work. For the development of the work some methods were used such as: Inductive, deductive, synthetic, analytical and explanatory, same that were applied in the different studies; Likewise, the survey technique was used to in order to primary information to determine the tastes and preferences of the users with respect the implementation of the community cabins. The presented proposal established guidelines for a sustainable and responsible community tourism, together with a single consequence of applying a business plan through a market study for the creation of Shanshun community cabins, which will contribute to the conservation of cultural wealth and of the area improving the living conditions of its inhabitants. According to the results of the Financial Evaluation it is determined that the project is feasible, since a Net Present Value of $ 203,772.67 is obtained, a value that is positive; a 25.13% Internal Rate of Return, a percentage that is greater than the opportunity cost; the benefit / cost relationship determines that for every dollar invested, fifty-five cents of the US dollar will be obtained; that the capital wii be 5 recovered in 4 years, 9 months and 17 days; the project according to the sensitivity analysis will support an increase in costs of 20.4% and a decrease in revenues of 13.20%, determining that the project is not sensitive and therefore is feasible. The Kichwa Association of the Limoncocha parish was socialized, which stated that it would act as a tool to comply the most important strategic objectives, to achieve a business structure, develop and strengthen the proposal of the creation of the tourist resort Hotel. And proceed to take possession in the tourist market of the canton and the province s since it is where the Business Plan is settled is a unique territory in Ecuador.